Individual Differences in Learning and Remembering - Eki Aprinaldi; Neviyarni Neviyarni (Jurnal Neo Konseling, 2021)
Humans or individuals are creatures that can be seen from a variety of viewpoints. An individual is a noun from an individual which means a person, individuals, and individuals. Individual differences, in general, are things that are relating to personal psychology that explains the psychological differences between people and their equals. Sources of individual differences are caused by innate factors and environmental factors. There are several different fields of difference individuals namely cognitive differences, differences in language skills, differences in motor skills, differences in background, differences in talent, differences in readiness defense, gender differences, personality differences, and learning style differences. Individual differences can be applied in several ways, namely using 12 educational services in accordance with the potential intelligence and special talents that are owned by students. Using an eclectic and flexible approach to advocacy, using a combination of cooperative learning, using multi-sensory tools to practice and obtain information.